Principal Leadership Strategy in Improving the Quality of Graduates Relevant to the Tourism Industry in Vocational High Schools (SMK) - Dahlia, Yunita; Asrin, Asrin; Setiadi, Dadi; Sudirman, Sudirman; Hakim, Mansur (International Journal of Education and Digital Learning (IJEDL), 2024)
This research aims to describe the Principal's Leadership Strategy in Improving the Quality of Graduates Relevant to the Tourism Industry in Vocational Schools. This research was conducted using field research and used a descriptive-qualitative approach. Data collection techniques, observation, interviews, questionnaires, and documentation. Meanwhile, data analysis involves data collection, data reduction, data presentation, and drawing conclusions. Data validity checks use credibility, transferability, dependability, and confirmability tests as data validity checks. The results of the research show that the leadership strategy of vocational school principals in improving the quality of graduates relevant to the tourism industry is by (1) Increasing Competent Teacher Resources by appointing teachers whose academic qualifications are in accordance with the tourism department, facilitating tourism teachers to take competency training, improving performance tourism teachers in carrying out their main duties, increasing teacher welfare, and carrying out supervision of tourism teachers. (2). Implementation of learning carried out in vocational schools, namely adapting the school curriculum to the needs of DUDI "Link and Match" teaching materials consisting of tourism theory and practice, implementing tourism learning based on digital technology, providing adequate learning facilities in accordance with industry standards.